2017
DOI: 10.1111/jocn.13746
|View full text |Cite
|
Sign up to set email alerts
|

Indian nurses in Italy: a qualitative study of their professional and social integration

Abstract: The research offers an insight into the complicated reasons for Indian nurses out-migration to Italy. Without comprehending the interwoven textures of the political and social relations that are continually constructed and re-constructed among different nations, it is difficult to understand nurses out-migration and consequently have a better and safer collaborative teamwork in the host countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 41 publications
4
14
1
10
Order By: Relevance
“…Participants in that study reported the conflicts that arose as a result of their experience with two distinct cultures. Similar findings have also been reported by Kankipati (2012) and Stievano et al (2017). The studies highlighted the difficulties of social integration by migrant Indians in the United States and migrant Indian nurses in Italy, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Participants in that study reported the conflicts that arose as a result of their experience with two distinct cultures. Similar findings have also been reported by Kankipati (2012) and Stievano et al (2017). The studies highlighted the difficulties of social integration by migrant Indians in the United States and migrant Indian nurses in Italy, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Nurse migration is a pivotal health issue with challenges that global communities have been aware of since the 1960s (Rosenkoetter et al 2017 ; Stievano et al 2017 ). This article outlines the main advantages of nurse migration but also highlights relevant human rights concerns that pertain to the issue.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this increase in migration is supported by the Indonesia-Japan Economic Partnership Agreement, which facilitates an easy and lucrative path for nurses educated in Indonesia to work in the destination country of Japan (Efendi et al 2017 ). Notably, resources for nurse education in source countries have economic significance (Stievano et al 2017 ; ten Have 2016 ). Fifty per cent of the nurses in the Indonesia-Japan agreement utilized Indonesian taxes and resources for education and training, which was subsidized for export to Japan and other countries (Efendi et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations